Curriculum and school praxis at the Union School of the Banking Association. Mendoza 1973-1976 (Praxis Educativa, 2020)
This paper seeks to introduce a reflection on the Escuela Sindical Bancaria, a union school founded by the Banking Association of Mendoza, which was the first Secondary Education Center opened in the province, in agreement with the National Direction of Adult Education (DINEA). We start with a brief history of the school and then focus on the construction of the Social Sciences Area, analyzing the bibliography used at the time and the specific mediations applied by the teachers in their classes. We conclude that trade union participation had a leading role in the school’s opening process and in the construction of its political significance. Regarding academic content, official guidelines for the Social Sciences Area were not followed, as a unique construction was developed. The research design was sociohistorical, based on oral and documentary sources.
Keywords: history of education; education for young and adults.